2003
DOI: 10.2174/0929866033479130
|View full text |Cite
|
Sign up to set email alerts
|

Renal Alterations Promoted By The Lectins From Canavalia Ensiformis (Cona) And Dioclea Guianensis (Dguil) Seeds

Abstract: The lectin from the seeds of Canavalia ensiformis (ConA) and Dioclea guianensis (DguiL) was tested upon its renal effects using the isolated perfusion rat kidney method. Both lectins (10 microg/ml) affected perfusion pressure and renal vascular resistance, but DguiL showed a much greater action than ConA. However, ConA, but not DguiL, affected potassium tubular transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…It has been shown that plant and animal lectins may promote inflammatory mediator release and that prostaglandin might interfere in sodium, potassium and chloride tubular transportation (27,28). In our experiments, indomethacin reversed the changes in the tubular transport of electrolytes induced by BmLec, suggesting the participation of eicosanoids in the process.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…It has been shown that plant and animal lectins may promote inflammatory mediator release and that prostaglandin might interfere in sodium, potassium and chloride tubular transportation (27,28). In our experiments, indomethacin reversed the changes in the tubular transport of electrolytes induced by BmLec, suggesting the participation of eicosanoids in the process.…”
Section: Discussionsupporting
confidence: 61%
“…In our experiments, indomethacin reversed the changes in the tubular transport of electrolytes induced by BmLec, suggesting the participation of eicosanoids in the process. In addition, the renal cortex produces prostaglandins that may inhibit tubular sodium reabsorption in the thick ascending limb of the loop of Henle and reduce chloride transport, thus exerting an influence on renal blood flow and glomerular filtration rate (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In respect to renal effects of Diocleinae lectins, our group demonstrated that the lectin of Canavalia brasiliensis (ConBr) (Teixeira et al, 2001), DguiL and ConA (Havt et al, 2003) distinctly alter physiological parameters in ex vivo rat kidneys. Considering that kidneys are responsible for the maintenance and excretion of electrolytes in the human body and the structure-activity relationship among Diocleinae lectins, the direct renal effects promoted by the seed lectin of Cratylia floribunda in isolated perfused kidneys and mesenteric bed of rats were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high degree of identity observed between the lectins isolated from seeds of the Diocleinae subtribe, they exhibit different biological activities (Alencar et al, 1999;Andrade et al, 1999;Assreuy et al, 1999;Cavada et al, 2001;Havt et al, 2003;Lopes et al, 2005). For instance, although concanavalin A (ConA) and Canavalia maritima lectin (ConM) possess 98% identity in primary sequence, they present different histamine-releasing activities, which is related to their affinity for biantennary complex oligosaccharides (Dam et al, 1998).…”
Section: Introductionmentioning
confidence: 99%